(untitled) (Analytical Methods for Drug Development, 2025)
Author Mrs. Indumathy Vemanna Assistant Professor, PG & Research Department of Biochemistry, Theivanai Ammal College for Women (A), Villupuram, Tamil Nadu, India Abstract Quality control methods ensure pharmaceutical products consistently meet established standards. Specifications development incorporates pharmacopeial requirements and in-house criteria with statistical approaches to acceptance limits based on manufacturing capability and clinical relevance. Method validation establishes accuracy, precision, specificity, and robustness parameters specifically for routine quality control environments. Statistical process control implements trend analysis and control charts for analytical results, enabling real-time process capability assessment and early detection of drift. Documentation systems include analytical method transfers, standard operating procedures, laboratory information management, and investigation protocols meeting regulatory requirements. Quality metrics track key performance indicators, manage out-of-specification results, and trend data for continuous improvement. Quality control data directly influences batch release decisions, process improvement initiatives, and regulatory compliance status. Implementation strategies balance analytical rigor with operational efficiency while maintaining data integrity and regulatory compliance across global manufacturing operations. Keywords: Pharmaceutical Quality, Analytical Method Transfer, Process Capability Analysis, Out-Of-Specification Investigation, Quality Control VIEW PDF